2016
DOI: 10.1016/j.annepidem.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The validity of self-reported behaviors: methods for estimating underreporting of risk behaviors

Abstract: Purpose When individuals underreport risk behaviors, data gathered from public health research and practice will underestimate risk. To date, there is little guidance on if or how reports can be adjusted to better reflect true levels of a risk behavior in a given cohort, sample or, by extension, population. Methods We develop the underreporting correction factor (UCF), which can be used to correct estimates of the prevalence of a risk behavior using self-report of the behavior and a specific (but not necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…In this study, we found substantial underreporting of unprotected sex compared to semen detection by PSA test. This finding is consistent with our prior study comparing biologic and self-reported measures of condomless sex in this cohort [46]. Self-reported condomless sex measures recalled behavior and willingness to report it.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found substantial underreporting of unprotected sex compared to semen detection by PSA test. This finding is consistent with our prior study comparing biologic and self-reported measures of condomless sex in this cohort [46]. Self-reported condomless sex measures recalled behavior and willingness to report it.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, partial‐mouth recording yields lower prevalence and severity rates (Eke, Thornton‐Evans, Wei, Borgnakke, & Dye, ; Kingman, Susin, & Albandar, ; Susin, Kingman, & Albandar, ). Fourth, interdental cleaning and toothbrushing were assessed through self‐reports, which are prone to measurement error and weaker associations (Norwood, Hughes, & Amico, ). Misclassification of exposure could have occurred if participants reporting favourable behaviours did not have enough manual dexterity to remove plaque effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, women using non-barrier modern contraceptives appear to report condomless sex more frequently than women not using a non-barrier method. This differential reporting could be related to HIV-positive women’s experience of stigma associated with pregnancy [ 26 ] [ 27 ]. As a result, women living with HIV may be more comfortable reporting condomless sex if they are using an additional non-barrier method of contraception to reduce their risk of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Women were asked about self-reported condomless sex in the past week, whereas detection of PSA is most sensitive within 24 hours, and may be detected up to 48 hours after condomless sex [ 18 ]. However, despite the shorter period captured by PSA detection compared to self-reported condomless sex, PSA was detected more often than self-reported condomless sex, suggesting substantial underreporting [ 26 ]. Fourth, the observational study design limits the ability to establish causal relationships.…”
Section: Discussionmentioning
confidence: 99%